2019
DOI: 10.1590/rbz4820180130
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction of F1 Holstein × Zebu cows in the final third of lactation modifies intake, nutrient digestibility, feeding behavior, and performance

Abstract: The objective of this study was to evaluate the effect of quantitative feed restriction level on nutrient intake and digestibility, nitrogen balance, efficiency and feeding behavior, and productive performance of F1 Holstein × Zebu cows in late lactation. Sixty F1 Holstein × Zebu cows were used at the stage of late lactation (183.0±17.5 days of lactation) and with initial body weight (BW) of 499±30 kg. The experimental arrangement adopted was the completely randomized design, with five feed restriction levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Applying a feed restriction to the least efficient cows may then improve their feed efficiency without compromising their production performance. Feed restriction is known to improve efficiency of nutrient use, with usually a significant decrease in milk volume and milk solids production (Ben Meir et al, 2019;Herve et al, 2019;Santana et al, 2019). In these studies, animals were all restricted at the same level.…”
Section: Introductionmentioning
confidence: 99%
“…Applying a feed restriction to the least efficient cows may then improve their feed efficiency without compromising their production performance. Feed restriction is known to improve efficiency of nutrient use, with usually a significant decrease in milk volume and milk solids production (Ben Meir et al, 2019;Herve et al, 2019;Santana et al, 2019). In these studies, animals were all restricted at the same level.…”
Section: Introductionmentioning
confidence: 99%
“…The higher iNDF concentration (227.4 g/kg) in the EGPS diet implies less fibrous fraction degradability, which limited the TDN intake in this diet, indicating lower energy availability for rumen fermentation (Borges et al 2019). However, Monção et al (2020 and Santana et al (2019Santana et al ( , 2020 recommended DMI for F1 Holstein/Zebu cows in the order of 2.50% BW. In this study, although lower DMI was found in cows that received the EGSP and SCPS diet, the DMI is above 2.50% BW not impairing the performance of the animals as justified by milk yield that did not change between treatments.…”
Section: Animals Feed Intakementioning
confidence: 99%
“…In the semiarid region of Brazil, sorghum silage (Sorghum bicolour (L.) Moench) It is traditionally used as a roughage (fibre source) for feedlot dairy cows due to tolerance to water restriction, mechanisable and high productivity per unit area and good nutritional value (Borges et al 2019). However, the feed cost under these conditions is high (Borges et al 2019;Santana et al 2019Santana et al , 2020. The use of traditional ingredients or byproducts and/or agribusiness wastes available in each region in the formulation of diets is a strategy to reduce feed costs and improve system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Isso ocorreu porque as condições edafoclimáticas, na maioria das regiões do país, tem favorecido a elevada produtividade de massa forrageira por unidade de área com bom valor nutricional, o que tem reduzido os custos com alimentação e, consequentemente, de produção (MONÇÃO et al 2019 ab). Entretanto, na região semiárida do Brasil ainda existem lacunas na produção animal (baixos índices zootécnicos) em função do déficit nutricional dos animais ruminantes, na maioria bovinos, devido aos longos períodos de estiagem, provocando variações na produção e qualidade da forragem ao longo do ano (MONÇÃO et al 2019a;SANTANA et al 2019).…”
Section: Introductionunclassified